2013
DOI: 10.1080/01635581.2013.804579
|View full text |Cite
|
Sign up to set email alerts
|

Decline of Lactate in Tumor Tissue After Ketogenic Diet: In Vivo Microdialysis Study in Patients with Head and Neck Cancer

Abstract: In head and neck squamous cell carcinoma (HNSCC) aerobic glycolysis is the key feature for energy supply of the tumor. Quantitative microdialysis (μD) offers an online method to measure parameters of the carbohydrate metabolism in vivo. The aim was to standardize a quantitative μD-study in patients with HNSCC and to prove if a ketogenic diet would differently influence the carbohydrate metabolism of the tumor tissue. Commercially available 100 kDa-CMA71-μD- catheters were implanted in tumor-free and in tumor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 18 publications
(15 reference statements)
0
33
0
4
Order By: Relevance
“…Based on the literature a synergistic effect of a carbohydrate-restricted diet with an anti-mitochondrial therapy can be concluded, since carbohydrate-restricted diets may induce enhanced OXPHOS and lead to inhibition of mTOR [218], which is responsible for synthesis of glycolytic enzymes [30,31]. Specifically observed in patients with head and neck cancer a ketogenic diet decreased the in vivo production of lactate in tumor cells [213]. …”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature a synergistic effect of a carbohydrate-restricted diet with an anti-mitochondrial therapy can be concluded, since carbohydrate-restricted diets may induce enhanced OXPHOS and lead to inhibition of mTOR [218], which is responsible for synthesis of glycolytic enzymes [30,31]. Specifically observed in patients with head and neck cancer a ketogenic diet decreased the in vivo production of lactate in tumor cells [213]. …”
Section: Discussionmentioning
confidence: 99%
“…This would be of special value for patients undergoing several week long radiotherapy during which prolonged fasting is no option. The state of ketosis, induced by low insulin levels, may generally benefit cancer patients, as KBs have been shown to inhibit glycolysis in various tumor cell lines 73, 74 and probably also patients, 75, 76, 77 and tumor cells often lack the enzymes 78, 79, 80, 81 or oxygenation 82 to effectively use ketones for energy production. Furthermore, in glioblastoma xenografts it was shown that KBs can partly reverse the genetic alterations that occur in these tumors.…”
Section: Insulin Igf-1 and Cancermentioning
confidence: 99%
“…A decrease in tumor lactate production has also been observed in mice kept on a KD [82,83] and in cultured cancer cells treated with ketone bodies [84,85] or fasting-mimicking conditions [86,87]. The decreased tumor lactate concentrations after a few days on a KD in head-and-neck cancer patients measured by Schroeder et al [81] are of particular interest, as tumor lactate concentrations have been directly linked to radioresistance in a variety of xenografted head-and-neck tumors that were irradiated using a clinically relevant schedule of 30 fractions over 6 weeks [88,89]. …”
Section: Combining Ketogenic Metabolic Therapy With Radiotherapy To Ementioning
confidence: 96%
“…In a case study of cancer patients, those who kept a strict KD showed reduced levels of the tumor marker TKTL-1 (transketolase-like 1), which is supposed to be associated with the pentose phosphate pathway [79]. Studies using FDG-PET imaging [25,80] or microdialysis measurements [81] have shown that a KD can downregulate the glycolytic tumor metabolism in some patients. A decrease in tumor lactate production has also been observed in mice kept on a KD [82,83] and in cultured cancer cells treated with ketone bodies [84,85] or fasting-mimicking conditions [86,87].…”
Section: Combining Ketogenic Metabolic Therapy With Radiotherapy To Ementioning
confidence: 99%